Variations in arterial supply via the external and internal carotid arteries to the bony orbit and eyeball in full-term fetuses, infants, children, adolescents, and adults – a South African perspective - Mpolokeng, Kentse Sana (Department of Human Biology, 2022)
The anatomy of the orbital region is of great importance for many highly specialised clinical disciplines such as ophthalmology, maxillofacial surgery, and neurosurgery. The main source of arterial blood supply to the orbital region is by the ophthalmic artery, a branch of the internal carotid artery, and to a lesser extent by the anastomotic patterns which are formed through the external carotid artery. A range of arterial variations which may be developmental in origin, or which may develop due to pathologies later in life, may affect the ophthalmic artery in terms of its origin, course, and branching. If clinicians are not aware of the variations occurring in this region, the eye of the patient may be at risk of injury during invasive procedures, which may lead to partial or complete visual loss. Up until the present time, there have been only a few cadaveric studies that revealed some of the variant patterns and the overall frequencies of the recorded anastomotic patterns for the orbital blood supply. Whilst the anatomical variations are known, the frequencies of variations in the population are not. Furthermore, no published data exists regarding the variations in the orbital blood supply in a South African population. Therefore, the aim of this study was to investigate the orbital vascular supply within the South Africans of different age groups, to document and describe any variations in anastomotic patterns and record their frequencies. The current study was conducted through dissections of bodies in the Department of Human Biology, University of Cape Town, and patients' angiograms from Groote Schuur Hospital. The angiograms included data obtained from other hospitals within the Cape Town area and were reviewed retrospectively. The dissection sample included six full term fetuses and 63 adults, and the angiograms accounted for 870 individuals. The ophthalmic artery was studied from the point of origin from the internal carotid artery and its course in relation to the optic nerve, and both sides were compared to note any similarities or differences. Statistical analyses were performed to record the frequencies of the patterns of variations and to note whether there were any associations between sex, age, sidedness, and these variations. The results revealed statistically significant associations between age and sex for the patterns of variation. Several variations were noted in the current study. Among the novel findings were those in the origin of the ophthalmic artery from the internal carotid artery, whereby a lateral and inferior origin were recorded in both samples (dissected bodies and angiograms). In addition, it was noted that the ophthalmic artery may take origin from the A2 segment of the anterior cerebral artery, which is also a novel finding. This study, therefore, adds significantly to the current body of knowledge regarding the patterns of arterial supply to the ophthalmic region in a South African sample.